The Development Interactive Multimedia Based on Problem based learning in Elementary Schools - Sekarwangi, Tunjung; Sartono, Kus Eddy; Mustadi, Ali; Abdulah, Abdulah (International Journal of Elementary Education, 2021)
Learning activities have an important role in student learning outcomes. Therefore, in learning activities, teachers must prepare quality learning. One of the efforts that can be made to improve the quality of learning is through the use of appropriate learning media. So that it can improve the process and better learning outcomes. This study uses a research and development (R&D) approach. This research was conducted at the Karangwuni Elementary School. The purpose of this research is to develop learning technology in the form of interactive multimedia based on problem based learning. The steps used in this research and development are the ADDIE development model. This research uses Macromedia Flash 8 application assistance to develop interactive multimedia based on problem based learning. The research data were obtained through the media validation sheet instrument by experts. The results of the media feasibility test based on the validation results obtained a feasibility value of 80%. Based on the results of the research that has been done, it can be concluded that interactive multimedia based on problem based learning is feasible to be applied in learning activities.